Economic relations between the EU and CIS (an overview) - Marek Dabrowski (Center for Social and Economic Research (CASE), 2007)
The purpose of this paper is to examine the economic aspects of EU policy towards its Eastern neighbors in the former Soviet Union. For a long period of time, this region was considered as less important for the EU, as compared to Central and Eastern Europe, which was the subject of a far-reaching economic and political integration offer materialized in two rounds of EU Eastern Enlargements (2004, 2007). However, moving the EU's geographical frontier further to the East and Southeast increased the importance of the CIS region as a potential partner of the enlarged EU. In 2004, East European and Caucasus countries were invited to participate in the European Neighborhood Policy a new EU external policy framework also addressed to the Southern Mediterranean countries. Russia has been attempting to build a strategic political and economic partnership with the EU outside the ENP framework but the content of this relationship is, in fact, very similar to the ENP. A general weakness of the ENP is that there is a lack of balance between farreaching expectations with respect to neighbors' policies and reforms, and limited and distant rewards that can potentially be offered. Thus, making this cooperation framework more effective requires a serious enhancement of the rewards using, to the extent possible, the positive experience of previous EU enlargements. The nature of contemporary economic relations in the globalized world calls for a more complex package-type approach to economic integration rather than just limiting cooperation to some narrow fields.
Keywords: F15; F21; F22; 330; EU-CIS relations; EU-Russia relations; EU and Central Asia; European Neighborhood Policy; Partnership and Cooperation Agreement; Wider Europe; EU-Politik; Internationale Wirtschaftsbeziehungen; EU-Nachbarstaaten; EU-Staaten; GUS-Staaten